2006
DOI: 10.1529/biophysj.106.085944
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Induced β-Amyloid Peptide Assemblage Fragmentation

Abstract: Alzheimer's disease is the most common cause of dementia and is widely believed to be due to the accumulation of beta-amyloid peptides (Abeta) and their interaction with the cell membrane. Abetas are hydrophobic peptides derived from the amyloid precursor proteins by proteolytic cleavage. After cleavage, these peptides are involved in a self-assembly-triggered conformational change. They are transformed into structures that bind to the cell membrane, causing cellular degeneration. However, it is not clear how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 55 publications
0
30
0
3
Order By: Relevance
“…Because A␤ oligomers are basically hydrophilic and do not settle well on graphite (15), we conclude that A␤ rafts are formed by a previously undescribed hydrophobic oligomeric species. TEM and AFM studies performed with artificial membranes have shown that, upon interaction with the membrane lipids, A␤ in fibrillar form reverts to globular peptide oligomers that associate into disordered domains (55). Thus, raft-forming oligomers could be part of a physiologically relevant pathway leading to the incorporation of soluble A␤ into cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Because A␤ oligomers are basically hydrophilic and do not settle well on graphite (15), we conclude that A␤ rafts are formed by a previously undescribed hydrophobic oligomeric species. TEM and AFM studies performed with artificial membranes have shown that, upon interaction with the membrane lipids, A␤ in fibrillar form reverts to globular peptide oligomers that associate into disordered domains (55). Thus, raft-forming oligomers could be part of a physiologically relevant pathway leading to the incorporation of soluble A␤ into cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…[57,58,59] It has been widely accepted that, depending on environmental conditions, such as pH, concentration, temperature, ionic strength, metal ions, and so forth, monomeric Ab can undergo a conformational change to form partially structured intermediates susceptible to fibril formation by a nucleation and growth process. [5,60] In this work, we determined the structures of AbA C H T U N G T R E N N U N G (1-40) in aqueous HFIP solutions at different pH, that has been reported as a model system for aggregation studies.…”
Section: Discussionmentioning
confidence: 99%
“…The peptide is affecting physicochemical properties of the membrane and, in turn, the membrane is affecting aggregations features of the peptide, hence neurodegeneration [7][8][9].…”
Section: Introductionmentioning
confidence: 99%